Similarity of Competitive Merchant Behavior Using the Jaccard Coefficient - Elveny, Marischa (UIN Sumatera Utara, 2020)
Advanced installment innovation has brought a business pattern that makes it simpler to see income conditions or what is known as a productive contrast. Different new ways are utilized to make progress, one of which is with an electronic-based business, yet with a particularly number of varieties, vulnerability in business is likewise progressively hard to foresee. Particularly foreseeing in the following not many years what exercises will regularly happen. Forecast itself is an interaction of efficiently assessing something that is well on the way to occur later on dependent on at various times data. To stay aware of the advancement of the organization, it is important to enhance the measurements for the business. Similarity involves the process of characterizing each object or describing in detail the features of the object. A way to measure similarity by characterizing each object so as to produce a similarity in behavior. used the jaccard method in finding similarities.